A comparison of usability testing methods for an e-commerce website: A case study on a Malaysia online gift shop - Goh, K.N. (2013)
Customer's perceived trust towards an e-commerce website is crucial for the success of online business. Effective design of web interfaces increases perceived trust of customers. Given many associated usability issues when performing tasks on a website, it is important for technopreneurs embarking on online business to understand issues related to usability problems of an e-commerce website and the techniques to identify these issues. In this study, usability evaluation was performed on an online gift shop with a group of potential consumers with age range of 18-22. Four different evaluation methods were used: Feedback Capture after Task (FCAT), Retrospective Think Aloud (RTA), Retrospective Think Aloud with Eye Movement (RTE) and observation. This study reveals that the major defects found were language and content, user guidance and support, flexibility and control, and visual clarity. Therefore, this study suggest that applying good user interface design could provide better user experience and thus increase perceived trust and user satisfaction towards the website. Â© 2013 IEEE.